2020
DOI: 10.1016/j.tibtech.2019.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Dunaliella Microalgae for Nutritional Protein: An Undervalued Asset

Abstract: β-carotene production with Dunaliella microalgae is established, yet their potential as protein source for food and feed applications seems overlooked. The rich protein content and nutritional tunability of Dunaliella make these algae intriguing sources of sustainable protein. It is of societal interest to exploit these promising proteinaceous Dunaliella traits. Dunaliella microalgae: Spotlighted β-carotene and undervalued protein Microalgae are recognized as promising sources for diversified applications incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 12 publications
1
25
0
Order By: Relevance
“…The amino acid content of microalgae varies significantly across species and strains, as shown with 38 screened microalgae [31]. Particularly, limited information is available regarding the amino acid contents in D. salina and the variation in amino acids as affected by cultivation conditions [8]. Becker (2007) [2] and Kent et al (2015) [3] demonstrated generally good protein quality of several microalgal species, including Dunaliella bardawil and a Dunaliella sp.…”
Section: Amino Acid Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amino acid content of microalgae varies significantly across species and strains, as shown with 38 screened microalgae [31]. Particularly, limited information is available regarding the amino acid contents in D. salina and the variation in amino acids as affected by cultivation conditions [8]. Becker (2007) [2] and Kent et al (2015) [3] demonstrated generally good protein quality of several microalgal species, including Dunaliella bardawil and a Dunaliella sp.…”
Section: Amino Acid Dynamicsmentioning
confidence: 99%
“…β-carotene, especially 9-cis β-carotene [ 5 ], is also amongst the most potent of carotenoids needed in the human diet to produce retinoids; these play important roles in cell differentiation, growth and apoptosis and are critical for controlling vision defects [ 6 , 7 ]. However, the potential of D. salina to be used as a protein source has gained increased attention in recent years, even after separation of carotenoids [ 6 , 8 ]. Depending on cultivation conditions, D. salina possesses a protein content of 57% (dry weight (DW) basis) or up to 80% on an ash-free dry weight (AFDW) basis [ 2 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Commercially, Dunaliella is cultivated in several countries, such as Australia, China, Israel, and India, with pilot-scale projects in Chile, Spain, Iran and Portugal [24][25][26] and considered one of the best sources of β carotene. Dunaliella has also been suggested as a sustainable source for industrial bioprocessing for the production of protein [27], biodiesel [4,28,29], colouring agent [30], and antioxidants [31].…”
Section: Introductionmentioning
confidence: 99%
“…As microalgae feed is thick and recalcitrant owing to cell wall with cellulose and polysaccharides, CAZymes are used as a flavor enhancer, which helps in food assimilation [ 173 ]. Microalgae species such as Nannochloropsis , Chlorella , Dunaliella , Haematococcus , and Schizochytrium with sizes of 25 µM or less are used as feed for zooplankton [ 174 , 175 ]. Shrimps feed entirely on microalgae and zooplankton during their metamorphosis.…”
Section: Functional Food/feedmentioning
confidence: 99%